INTERNATIONAL DECADE OF INDIGENOUS LANGUAGES IN THE CONTEXT OF ETHNOPOLITICAL PROCESSES - A. A. Vartumyan; A. V. Mankieva; M. G. Pavlova (Современная наука и инновации, 2022)
Globalization and the emerging information society contribute to the perturbation of societies on a planetary scale, changing the habits and traditions of peoples and ethnic groups. The changes also affect many indigenous peoples around the world, who are increasingly marginalized and in the process of transformation lose touch with their native languages. Some indigenous peoples have to experience problems related to climate change or forced relocation, an unfavorable educational situation and illiteracy. Migration processes, various forms of discrimination, environmental disasters and other bifurcations also negatively affect the development of indigenous languages. It is concluded that at present there is a risk that indigenous languages will fall out of everyday use, and problems related to indigenous languages can have much broader consequences, affecting a wide range of areas.